An updated duet model for passage re-ranking - Mitra, Bhaskar; Craswell, Nick (2019)
We propose several small modifications to Duet—a deep neural ranking model—and evaluate the updated model on the MS MARCO passage ranking task. We report significant improvements from the proposed changes based on an ablation study.